2021
DOI: 10.3390/ijerph18052231
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of COVID-19 Symptoms among U.S. Adults with Allergies

Abstract: Background: This study sought to evaluate COVID-19 associated physical and mental health symptoms among adults with allergies compared to the general U.S. adult population. Methods: Data for these analyses were obtained from the publicly available COVID-19 Household Impact Survey, which provides national and regional statistics about physical health, mental health, economic security, and social dynamics among U.S. adults (ages 18 and older). Data from 20–26 April 2020; 4–10 May 2020; and 30 May–8 June 2020 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Our study findings also demonstrated increased reports of physical health symptoms among individuals with chronic respiratory conditions. Some of the physical symptoms reported an overlap with several symptoms common to the respiratory conditions themselves including coughing, sneezing, fatigue/tiredness, and shortness of breath [24][25][26]. Adults with COPD and asthma had a particularly higher prevalence of nausea, vomiting/diarrhea, and fatigue/tiredness.…”
Section: Discussionmentioning
confidence: 99%
“…Our study findings also demonstrated increased reports of physical health symptoms among individuals with chronic respiratory conditions. Some of the physical symptoms reported an overlap with several symptoms common to the respiratory conditions themselves including coughing, sneezing, fatigue/tiredness, and shortness of breath [24][25][26]. Adults with COPD and asthma had a particularly higher prevalence of nausea, vomiting/diarrhea, and fatigue/tiredness.…”
Section: Discussionmentioning
confidence: 99%
“…A survey item assessing the prevalence of symptoms of physical anxiety linked to the COVID-19 outbreak was used to assess pandemic anxiety [ 26 , 27 ]. The survey question asked participants how often they had physical anxiety symptoms over a certain week, reflecting their COVID-19 experience: “In the past 7 days, have you had physical reactions, such as sweating, trouble breathing, nausea, or a pounding heart, when thinking about your experience with the COVID-19 pandemic?” Participants chose from the following list of options: rarely or none of the time (less than 1 day), some or a little of the time (1-2 days), occasionally or a moderate amount of time (3-4 days), or most or all of the time (5-7 days).…”
Section: Methodsmentioning
confidence: 99%
“…8 Adults with self-reported physiciandiagnosed allergies and asthma are more likely to report feelings of nervousness (crude [c]OR, 1.34; 95% CI, 1.13-1.60), depression (cOR, 1.32; 95% CI, 1.11-1.57), loneliness (cOR, 1.23; 95% CI, 1.04-1.47), and hopelessness (cOR, 1.44; 95% CI, 1.21-1.72) compared with those without allergies during COVID-19. 9 These studies have revealed that people with allergic diseases had a higher negative psychological impact as a result of the pandemic. 8,9 These findings have important implications for diagnostic and treatment challenges for physicians who care for people with allergic diseases and will be further explored in this review.…”
Section: Introductionmentioning
confidence: 99%
“…9 These studies have revealed that people with allergic diseases had a higher negative psychological impact as a result of the pandemic. 8,9 These findings have important implications for diagnostic and treatment challenges for physicians who care for people with allergic diseases and will be further explored in this review. Lastly, tackling COVID-19 vaccine hesitancy owing to perceived allergy has been an ongoing challenge for allergists; however, many individuals, including those who reacted to their first dose, with some exceptions, can safely receive the second dose in a controlled setting.…”
Section: Introductionmentioning
confidence: 99%